(untitled) (Journal of Applied Learning and Teaching, 2019)
Our study evaluated the integration of gamified laboratory (game-lab) simulations and virtual reality (VR) technologies into the biology curriculum in order to provide an engaging and interactive way for Gen Z (born after 1995) students to learn and understand key biology concepts in a simulated environment. We hypothesised that the students will have fun, learning through play and exploration of lab skills that may not be possible in standard educational settings. Our research question was, “Do VR game-lab simulations lead to an increase in a) student knowledge of DNA-based technology, b) intrinsic motivation to study key biological concepts, and c) self-efficacy in an introductory biology course?” In our study conducted at the Singapore University of Technology and Design, the freshmore (ages between 19-22) cohorts were randomly divided into three groups, control (n = 180 students), VR game-lab simulations experienced on a laptop (desktop VR, n = 180 students) and experienced using a headset (immersive VR, n = 90 students). The classes assigned to the control group were taught using the prior method (PowerPoint slides/chalk and talk). The biological concept covered was consistent in all groups and was the polymerase chain reaction taught using a crime scene investigation scenario. Data collected showed that the desktop VR group of students achieved the greatest improvement in quiz scores after the simulation as compared to controls and immersive VR. This correlated with the significantly reduced response times taken for quizzes too for the desktop VR group. This may be attributed to the fact that the desktop VR was a longer simulation, with in depth theoretical wikis and descriptions of relevant theory. The survey results revealed that the majority of students perceived that the simulations improved their learning of DNA-based technologies, were motivated to complete the simulation and felt more confident at the end.